CASE OF AVIAN INFLUENZA IN BROILER CHICKEN AT JATILUWIH VILLAGE - Alya Nita Shena Gayanti; I Gusti Ngurah Kade Mahardika; Ida Bagus Oka Winaya; I Gusti Ketut Suarjana; Ida Ayu Pasti Apsari (Buletin Veteriner Udayana, 2024)
Avian Influenza (AI) is still endemic in Bali. This disease is very dangerous and deadly, is zoonotic in birds and humans and causes high economic losses. AI disease in poultry is caused by the Influenza virus type A. The aim of the examination is to identify the agent that caused the death of the chicken in the case to determine a definite diagnosis. The case chicken sample was a 29 day old broiler chicken from a farm in Jatiluwih Village, Tabanan Regency, Bali. Clinical symptoms of chickens include: weak chickens, shaking, shortness of breath, no appetite for eating or drinking, dull feathers, pale bluish combs, runny discharge from the beak, and white-brown watery feces. Chicken death occurred 2 days after clinical symptoms appeared. After the chicken dies, a necropsy is carried out and the samples are examined in the histopathology, virology, bacteriology and parasitology laboratories to determine the agent that caused the death. Histopathological examination showed that all organs had lesions. The results of the HA/HI test showed that the chicken was a positive case of being infected with the Avian Influenza virus. Bacterial infection testing in the media test, selective test, primary test, secondary test and confectionery test identified the presence of Staphylococcus sp bacteria. in the liver and lungs. The results of fecal examination during parasite examination using native and concentration methods did not reveal any worm eggs or protozoa. It was concluded that the case chicken was infected with Avian Influenza with secondary bacterial infection, namely Staphylococcus sp. It is recommended that breeders improve biosecurity and carry out routine and appropriate vaccinations to prevent Avian Influenza disease.